Differences in Hematocrit and Leukocyte Levels in Preeclampsia and Severe Preeclampsia - Wiwit Indriyani Aslina; Yuni Riska Hadi (Professional Health Journal)
Introduction:  Preeclampsia is a serious pregnancy complication characterized by hypertension occurring at a gestational age of ≥ 20 weeks. In preeclampsia, hematological changes occur due to vasospasm. Vasospasm leads to endothelial damage of blood vessels, marked by an increase in hematocrit and leukocyte levels.